Comparative Analysis of Clinical-Scale IFN-γ-Positive T-Cell Enrichment Using Partially and Fully Integrated Platforms - Priesner, Christoph (Front Immunol, 2016)
BACKGROUND AND AIMS: The infusion of enriched CMV-specific donor T-cells appears to be a suitable alternative for the treatment of drug-resistant CMV reactivation or de novo infection after both solid organ and hematopoietic stem cell transplantation. Antiviral lymphocytes can be selected from apheresis products using the CliniMACS Cytokine-Capture-System(®) either with the well-established CliniMACS(®) Plus (Plus) device or with its more versatile successor CliniMACS Prodigy(®) (Prodigy). METHODS: Manufacturing of CMV-specific T-cells was carried out with the Prodigy and Plus in parallel starting with 0.8–1 × 10(9) leukocytes collected by lymphapheresis (n = 3) and using the MACS GMP PepTivator(®) HCMVpp65 for antigenic restimulation. Target and non-target cells were quantified by a newly developed single-platform assessment and gating strategy using positive (CD3/CD4/CD8/CD45/IFN-γ), negative (CD14/CD19/CD56), and dead cell (7-AAD) discriminators. RESULTS: Both devices produced largely similar results for target cell viabilities: 37.2–52.2% (Prodigy) vs. 51.1–62.1% (Plus) CD45(+)/7-AAD(−) cells. Absolute numbers of isolated target cells were 0.1–3.8 × 10(6) viable IFN-γ(+) CD3(+) T-cells. The corresponding proportions of IFN-γ(+) CD3(+) T-cells ranged between 19.2 and 95.1% among total CD3(+) T-cells and represented recoveries of 41.9–87.6%. Within two parallel processes, predominantly IFN-γ(+) CD3(+)CD8(+) cytotoxic T-cells were enriched compared to one process that yielded a higher amount of IFN-γ(+) CD3(+)CD4(+) helper T lymphocytes. T-cell purity was higher for the Prodigies products that displayed a lower content of contaminating IFN-γ(−) T-cells (3.6–20.8%) compared to the Plus products (19.9–80.0%). CONCLUSION: The manufacturing process on the Prodigy saved both process and hands-on time due to its higher process integration and ability for unattended operation. Although the usage of both instruments yielded comparable results, the lower content of residual IFN-γ(−) T-cells in the target fractions produced with the Prodigy may allow for a higher dosage of CMV-specific donor T-cells without increasing the risk for graft-versus-host disease.